2019
DOI: 10.1002/smi.2903
|View full text |Cite
|
Sign up to set email alerts
|

Psychological stress reduces the immunological benefits of breast milk

Abstract: Our study aimed to assess the impact of maternal psychological stress on the immunological components of breast milk. Eighty‐nine women participated in the study. We assessed general stress, postpartum‐specific stress, negative affectivity, salivary cortisol of mother, and secretory immunoglobulin A (sIgA) levels of breast milk 4–6 weeks after delivery. Controlling for the effects of women's age, weight, number, and duration of feedings, postpartum‐specific stress was related to reduced sIgA concentration (R2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…The most abundant antibody found in human milk is secretory immunoglobulin A (IgA), which plays a major role in mucosal immunity as a first line of defense against many pathogens (Schlaudecker et al, 2013). IgA levels vary between women and are influenced by multiple factors, including lactation stage, gestational age at delivery, and maternal factors, including stress, food intake, and exercise (Moirasgenti et al, 2019;Saso & Kampmann, 2020;Urwin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The most abundant antibody found in human milk is secretory immunoglobulin A (IgA), which plays a major role in mucosal immunity as a first line of defense against many pathogens (Schlaudecker et al, 2013). IgA levels vary between women and are influenced by multiple factors, including lactation stage, gestational age at delivery, and maternal factors, including stress, food intake, and exercise (Moirasgenti et al, 2019;Saso & Kampmann, 2020;Urwin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Higher SIgA is associated with mental state [30]. Positive correlation between psychological stress and cortisol levels and negative association between psychological stress and SIgA levels [31]. Oshima et al reported acute physiological training stress was observed an increase in plasma resting cortisol concentration [32].…”
Section: Discussionmentioning
confidence: 98%
“…Higher SIgA is associated with mental state [31]. There is a positive correlation between psychological stress and cortisol levels and a negative association between psychological stress and SIgA levels [32]. Oshima et al reported that acute physiological training stress resulted in an increase in resting plasma cortisol concentration [17].…”
Section: Discussionmentioning
confidence: 99%